Determinants of recession on the non-bank loans market in Poland - Waliszewski, Krzysztof (Journal of Finance and Financial Law, 2020)
The tightening of banking regulations in the field of retail lending (recommendations of the Polish Financial Supervision Authority) led to a dynamic growth in the non-bank loans sector in Poland. In addition to the traditional (off-line) segment of loans granted at home and in stationary outlets – own and partner ones, e.g. through financial intermediaries in connection with the development of modern technologies in consumer finance (fin-tech), the remotely granted loans segment has been dynamically developed (on-line, digital lending, Lend-tech). During the dynamic growth of the loan sector, a number of prudential and loan consumer protection regulations entered into force, and the largest loan institutions were covered by the so-called bank tax. However, loan market statistics for 2019 show that from month to month the sales dynamics of non-bank loans fell to reach negative values at the end of the year, which in practice means a state of recession on this market. The purpose of the article is to identify the determinants of the recession of the non-bank loans market observed in 2019. The article uses literature on the subject, which consists of legal acts, scientific articles, reports and statistical data.